2018
DOI: 10.3382/ps/pex308
|View full text |Cite
|
Sign up to set email alerts
|

Yellow mealworm larvae (Tenebrio molitor) inclusion in diets for male broiler chickens: effects on growth performance, gut morphology, and histological findings

Abstract: This study evaluated the effects of Tenebrio molitor (TM) larvae meal inclusion in diets for broilers. A total of 160 male broiler chicks (Ross 708) at one-day of age were randomly allotted to four dietary treatments: a control (C) group and three TM groups, in which TM meal was included at 50 (TM5), 100 (TM10), and 150 (TM15) g/kg, respectively. The experimental diets were isonitrogenous and isoenergetic. Each group consisted of five pens as replicates (8 chicks/pen). After the evaluation of growth performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
116
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 31 publications
20
116
3
7
Order By: Relevance
“…Moreover, the unquestionable shift from a conventional protein source (soybean) to TM meal was observed and it may demonstrate that birds opted to feed on TM meal because of its sensory characteristics as well as good nutritional profile. Accordingly, Biasato et al [41] suggested that improved diet palatability might be responsible for the increased feed intake and weight gain when chickens were fed TM meal in their study.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the unquestionable shift from a conventional protein source (soybean) to TM meal was observed and it may demonstrate that birds opted to feed on TM meal because of its sensory characteristics as well as good nutritional profile. Accordingly, Biasato et al [41] suggested that improved diet palatability might be responsible for the increased feed intake and weight gain when chickens were fed TM meal in their study.…”
Section: Discussionmentioning
confidence: 89%
“…Bovera et al (2015) reported that there was no difference in the body weight and body weight gain of the broilers between the group fed with mealworm meal containing rations and the control group. Biasato et al (2018) suggested that the addition of 5, 10 and 15% mealworm to diet in male broiler may improve body weight and feed intake, but may adversely affect feed efficiency, so researchers suggested that low levels of mealworm addition to the diet may be more appropriate. The researchers also reported that there was no significant difference in carcass characteristics between the treatment group and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Biasato et al (2016) confirmed that the inclusion of the yellow meal worm did not affect the performance of free-range chickens, so that mealworm could be used safely in poultry diets. In another study, these researchers (Biasato et al, 2018) suggested that increasing levels of dietary mealworm meal inclusion Performance and carcass traits of quails fed by diets containing mealworms were investigated. A total of 200 mixed-sex one-day-old quail chicks were used in the study.…”
Section: Intrоduсtiоnmentioning
confidence: 99%
“…Overall, insects are generally rich in proteins (30-68% on dry matter, DM) with well-balanced amino acid profiles (Finke 2015;Gasco et al 2018a;Koutsos et al 2019). In addition, they result promising as a fat/ energy source (Wang and Shelomi 2017;Biasato et al 2018;Schiavone et al 2018;Gasco et al 2019b) being rich in lipids (about 10 to 30% on DM), though their fatty acid profile is highly variable. Insects can be considered also a good source of vitamins (especially vitamin B 12 ) and bioavailable minerals, particularly iron and zinc (Finke 2015;Payne et al 2016).…”
Section: Strengthsmentioning
confidence: 99%